SCIENTIFIC APPROACH RESILIENCE IN ELEMENTARY SCHOOL THROUGH DEVELOPMENT OF LAPBOOK LEARNING MEDIA - Zariul Antosa; Lazim N (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
lapbook learning media. The research method uses the 4 D research and development model consists of four stages: define, design, develop, and disseminate. The research instrument used attitude scale measurement parameters raised by Likert. This research produces lapbook learning media which is used in thematic learning in elementary schools. The development of lapbook learning media has been developed through the stages of validation by expert judgment with an average value of 88.87% with a very decent category. Material experts give a score of 87%, linguists 85%, 88.5% presentation and graphic experts give a score of 95 all with very decent categories. After being tested for a limited test in grade 1 elementary school the response value of 84.50% was obtained with a very good category. From the research data it can be concluded that this lapbook learning media has very good quality as a medium for thematic learning in low grade